Antenatal ultrasonography should be for all. Phocomelia: An extremely rare congenital anomaly- A case report - Pradyumna Pan (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2019)
While rarely seen in the present-day, Phocomelia syndrome is a sporadic congenital malformation disrupting the normal growth and progressing of the musculoskeletal system.